12-Week Treatment with LY2409021 Significantly Lowers HbA1C and Is Well Tolerated in Patients with Type 2 Diabetes Mellitus - Vinall, Maria (MD Conference Express, 2012)
The glucagon receptor antagonist LY2409021 (LY) substantially lowers HbA1C without severe hypoglycemia or weight gain in type 2 diabetes mellitus (T2DM) patients. In a double-blind, randomized, placebo-controlled, Phase 2 study researchers examined the margin between LY efficacy and safety by comparing mean changes in HbA1C and liver aminotransferases at 3 dose levels.